Craniovertebral realignment for basilar invagination - Atul Goel (Indian Journal of Neurosurgery)
The understanding of pathogenesis and treatment of basilar invagination has been evolving for over a century. The concepts regarding nature of atlantoaxial instability in such cases are also under discussion. The author presents personal evolving concepts on the subject. The technique of craniovertebral realigement, its rationale and the outcome of treatment is presented.